Principal Management in Enhancing the Work Discipline of Elementary School Teachers - Dede Tupah Mulyani; Deti Rostini (CV. Media Digital Publikasi Indonesia, 2026)
Teacher work discipline is a critical determinant of educational quality, yet it remains a significant challenge in many schools. The principal's managerial role is central to fostering a culture of discipline. This study was prompted by the need to understand how systematic management can address issues of teacher indiscipline. The purpose of this research is to analyze how a principal's management, guided by the Plan-Do-Check-Act (PDCA) cycle, enhances teacher work discipline. This study employed a qualitative approach with a single-case study design at Sukahegar Public Elementary School in Cianjur, Indonesia. Data were collected through in-depth interviews with the principal and teachers, non-participant observations of school operations, and an analysis of institutional documents. Data credibility was ensured through source and technique triangulation, with the analysis following the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the principal’s management systematically followed the PDCA cycle. The Plan phase involved data-driven problem identification and the collaborative development of a discipline program. The Do phase saw the consistent implementation of this plan through direct supervision, role modeling, and a reward system. The Check phase consisted of continuous monitoring and formal evaluation of teacher attendance and performance. The Act phase involved providing targeted coaching and making systemic policy adjustments based on evaluation data. The principal's systematic application of the PDCA management cycle proved highly effective in improving teacher work discipline, leading to enhanced punctuality, instructional readiness, and administrative compliance. This study concludes that a structured, continuous improvement approach to management is a powerful tool for principals to cultivate a professional and disciplined work culture, thereby elevating the overall quality of education.